2014
DOI: 10.1080/14623943.2014.944136
|View full text |Cite
|
Sign up to set email alerts
|

Developing leadership identity through critical reflection: voice, knowledge and advocacy

Abstract: This article describes the leadership identity development of an American Latina teacher as she moves from the domain of her classroom outward to lead her grade level team, school leadership team and school district personnel. The leadership master's degree programme is grounded in transformative learning theory, emphasizes social justice and equity, and employs systematic critical reflection. Through structured critical reflections over two years, Cecilia examines her own experiences as a student and teacher,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…">A quality assessment was made and reasons for inclusion and exclusion were listed. Examples of exclusions included studies whose data was analysis of policy documents Spicksley (2022)* or those predominantly focused on a concept other than identity for example, leadership Collay (2014). …”
Section: Methodsmentioning
confidence: 99%
“…">A quality assessment was made and reasons for inclusion and exclusion were listed. Examples of exclusions included studies whose data was analysis of policy documents Spicksley (2022)* or those predominantly focused on a concept other than identity for example, leadership Collay (2014). …”
Section: Methodsmentioning
confidence: 99%
“…For example, based on their case study of school sites in which critical reflection was used to help teachers examine their teaching practice, Saito and Khong (2017) found that over time participants became less likely to hold deficit views of students and more likely to consider their own roles in students’ struggles. Similarly, in a study of education leadership students in a program that emphasized critical reflection, Collay (2014) found that it bolstered participants’ abilities and desires to advocate for marginalized students.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Critical reflection scholars and MSJTE scholars have highlighted the importance of critical reflection in teacher education. Answering Sleeter’s (1996) call to frame multicultural education as social activism, critical reflection can strengthen educators’ agency as advocates of justice-oriented change (Collay, 2014; Felton & Koestler, 2015). This might include spotting and dismantling deficit views of students experiencing poverty (Morgan, 2017), helping students develop critical media literacy by examining the influence of power on knowledge (Smith, 2011), or challenging unjust policies or practices in their schools (Ross, 2015)—which have been linked to students’ exposure to critical reflection.…”
Section: Literature Reviewmentioning
confidence: 99%
“…With the exception of those studies that examine the learning experiences of justice-oriented teacher leaders, including attention to critical consciousness (Bradley-Levine, 2012;Collay, 2014), LGB [sic] issues (Larrabee & Morehead, 2010), and critical race professional development (Kohli, 2019), there is scant scholarship that emphasizes teacher leadership learning through a lens of race and power. Without clarity in research and practice of what constitutes "teacher leadership" as situated within structures that normalize whiteness, perceived leadership legitimizes hegemonic, narrow, apolitical, and incorrect assumptions of what and who constitutes a "leader" for educational justice (Scribner & Bradley-Levine, 2010).…”
Section: Intertwined Tales Of Teacher Leadershipmentioning
confidence: 99%